THE LEGEND OF “GUNUNG WURUNG” AS LOCAL WISDOM FOR TEACHING MATERIALS AND CHARACTER EDUCATION IN ELEMENTARY SCHOOL - Ngatman, Ngatman; Fatimah, Siti (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Natural phenomena formed on earth such as the formation of mountains can be used as a means for humans to always think and increase curiosity. In the world of education, natural phenomena can be used as a medium for learning. This study aims to analyze and study the legend of Gunung Wurung as a teaching material based on local wisdom and strengthening the character education in elementary school. The legend of Gunung Wurung is one of the folklore located Karangsambung area, Kebumen, Central Java. This research is a descriptive research. The research data was obtained from the results of observations and interviews with residents around the Karangsambung area and the results of the teacher perception questionnaire SDN 02 Kuwayuhan. Data analysis techniques used a qualitative descriptive approach. The results of the analysis show that: 1) The legend of Gunung Wurung turned out to be less well known to residents around the Karangsambung area; 2) The legend of Gunung Wurung can be used as an alternative material in thematic learning in elementary schools based on local wisdom; 2) Character education values in the legend of Gunung Wurung include religious character, respect and obedience, cooperation, hard work, social care, patience, and commitment.